2021
DOI: 10.1093/nar/gkab098
|View full text |Cite
|
Sign up to set email alerts
|

Intron exon boundary junctions in human genome have in-built unique structural and energetic signals

Abstract: Precise identification of correct exon–intron boundaries is a prerequisite to analyze the location and structure of genes. The existing framework for genomic signals, delineating exon and introns in a genomic segment, seems insufficient, predominantly due to poor sequence consensus as well as limitations of training on available experimental data sets. We present here a novel concept for characterizing exon–intron boundaries in genomic segments on the basis of structural and energetic properties. We analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…7 Like promoter identification, detecting accurate intron-exon architecture within a gene is essential and has recently received significant attention in eukaryotic genome annotation. 17 The primary focus of categorization was on the splice sites (SSs) and junction sequences. Conventionally, it includes a G-T nucleotide pair at the 5 0 end of the intron, and an A-G nucleotide pair at the 3 0 end.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 Like promoter identification, detecting accurate intron-exon architecture within a gene is essential and has recently received significant attention in eukaryotic genome annotation. 17 The primary focus of categorization was on the splice sites (SSs) and junction sequences. Conventionally, it includes a G-T nucleotide pair at the 5 0 end of the intron, and an A-G nucleotide pair at the 3 0 end.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, it includes a G-T nucleotide pair at the 5 0 end of the intron, and an A-G nucleotide pair at the 3 0 end. 7,17 With the continuous characterization of SSs, many sequence alterations occur at these sites. Further, the identification of the exon-intron junctions becomes challenging due to the presence of alternative splicing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Global structural properties such as DNA bending (intrinsic curvature and ligand‐induced bending or flexibility), DNA duplex stability, supercoil‐induced DNA destabilization and topology have been characterized at more than one helical turn of DNA [49]. Several experimental and high‐throughput computational studies revealed that unique stability, flexibility and curvature of DNA sequences play key roles in physiological processes like the orchestration of transcription and replication machinery [53–59]. Of note, the DNA compaction which results in proximal rearrangement of long stretches of DNA might be dependent on anisotropic DNA structures by lowering the free energy of the transitions.…”
mentioning
confidence: 99%